Survival of SARS‐CoV‐2 in artificial seawater and on the surface of inanimate materials. Issue 8 (5th May 2022) - Sun, Zhi‐Ping; Yang, Si‐Yu; Cai, Xia; Han, Wen‐Dong; Hu, Gao‐Wei; Qian, Yun; Wang, Yu‐Yan; Zhang, Rong; Xie, You‐Hua; Qu, Di
Abstract: There is a potential risk for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) spread through human contact with seafood and the inanimate materials contaminated by the virus. In this study, we examined the stability of the virus in artificial seawater (ASW) and on the surface of selected materials. SARS‐CoV‐2 (3.75 log10 TCID50 ) in ASW at 22℃ maintained infectious about 3 days and at 4℃ the virus survived more than 7 days. It should be noticed that viable virus at high titer (5.50 log10 TCID50 ) may survive more than 20 days in ASW at 4℃ and for 7 days at 22℃. SARS‐CoV‐2 on stainless steel and plastic bag maintained infectious for 3 days, and on nonwoven fabric for 1 day at 22℃. In addition, the virus remained infectious for 9 days on stainless steel and non‐woven fabric, and on plastic bag for 12 days at 4℃. It is important to highlight the role of inanimate material surfaces as a source of infection and the necessity for surface decontamination and disinfection.